Perancangan UI/UX Aplikasi Layanan Desa Berbasis Mobile dengan Double Diamond dan SUS - Fahrul Firgiana; Kusnadi Kusnadi; Rifqi Fahrudin (Lembaga Pengembangan Kinerja Dosen, 2025)
Limited access to public information in rural areas is a barrier to achieving transparency and responsive government services. This study aims to design the user interface and user experience (UI/UX) of a mobile-based village service application to facilitate public access to services and information digitally. The Double Diamond approach was used to identify problems and develop user-centered design solutions. Usability testing was conducted using the System Usability Scale (SUS) method on five respondents with diverse age, occupation, and digital literacy backgrounds. The study focused on developing key features, such as letter submission, village announcements, public complaints, budget transparency, village news, and integrated health post (Posyandu) schedules. The results of the study were an application prototype with a simple, easy-to-use interface that aligns with the digital habits of village residents. Based on the SUS testing, the prototype obtained an average score of 85, indicating excellent usability and user acceptance. These findings suggest that a user-centered design approach can improve the quality of digital public services at the village level. For future research, it is recommended to involve more respondents from diverse backgrounds and consider other evaluation methods, such as the User Experience Questionnaire (UEQ) or Heuristic Evaluation, to gain a deeper understanding of the quality and comfort of the user interface. Furthermore, this research also has practical contributions in supporting digital transformation in rural areas. Keywords: Double Diamond; SUS; UI/UX; Usability; Village App Limited access to public information in rural areas is a barrier to achieving transparency and responsive government services. This study aims to design the user interface and user experience (UI/UX) of a mobile-based village service application to facilitate public access to services and information digitally. The Double Diamond approach was used to identify problems and develop user-centered design solutions. Usability testing was conducted using the System Usability Scale (SUS) method on five respondents with diverse age, occupation, and digital literacy backgrounds. The study focused on developing key features, such as letter submission, village announcements, public complaints, budget transparency, village news, and integrated health post (Posyandu) schedules. The results of the study were an application prototype with a simple, easy-to-use interface that aligns with the digital habits of village residents. Based on the SUS testing, the prototype obtained an average score of 85, indicating excellent usability and user acceptance. These findings suggest that a user-centered design approach can improve the quality of digital public services at the village level. For future research, it is recommended to involve more respondents from diverse backgrounds and consider other evaluation methods, such as the User Experience Questionnaire (UEQ) or Heuristic Evaluation, to gain a deeper understanding of the quality and comfort of the user interface. Furthermore, this research also has practical contributions in supporting digital transformation in rural areas.